2010
DOI: 10.4038/jnsfsr.v38i4.2648
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of Coscinium fenestratum (Gaertn.) Colebr. (Menispermaceae) - an endangered medicinal plant

Abstract: Coscinium fenestratum (Gaertn.) Colebr. is an important medicinal plant belonging to the family Menispermaceae. Multiple shoots were formed from epicotyl explants on Murashige and Skoog (MS) medium supplemented with 1.0 µM kinetin (Kin) and 0.25 µM 2,4-Dichlorophenoxy acetic acid (2,4-D). A maximum of five shoots were obtained from one explant in a 75-day culture period. The effect of subsequent subcultures on shoot formation was also studied. Repeated subculture favoured the increase in shoot length and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…It is seen that IBA is effective against rooting of callus whereas added application of ZnSO 4 at concentration 3 mg/ml along with IBA 2 mg/ml in combinations showed direct rooting in stem within 18 days in half strength MS medium mixed with coconut water (Table 2, Figure 4). Literature survey revealed that root initiation occurred after the 3rd week of transferring the shoots to the rooting medium and the rooting percentage greatly depends on strength of MS medium (Senarath, 2010). Our results showed rooting of stem occurred within 18 days which is lesser time than that of reported earlier.…”
Section: Effect Of Different Combinations Of Auxin Cytokinins Andmentioning
confidence: 39%
See 1 more Smart Citation
“…It is seen that IBA is effective against rooting of callus whereas added application of ZnSO 4 at concentration 3 mg/ml along with IBA 2 mg/ml in combinations showed direct rooting in stem within 18 days in half strength MS medium mixed with coconut water (Table 2, Figure 4). Literature survey revealed that root initiation occurred after the 3rd week of transferring the shoots to the rooting medium and the rooting percentage greatly depends on strength of MS medium (Senarath, 2010). Our results showed rooting of stem occurred within 18 days which is lesser time than that of reported earlier.…”
Section: Effect Of Different Combinations Of Auxin Cytokinins Andmentioning
confidence: 39%
“…These difficulties are only overcome through in vitro cultivation. There are few reports on cell and suspension culture of this plant by which shoots and roots are developed (Parthasarathy, 2007;Staden et al, 2008) and also reported increased amount of berberine content, estimated by HPLC method (Talat et al, 2009;Senarath, 2010). In another study, it is revealed that petiole and leaf explants of CF formed callus on vermi-compost extract media along with coelomic fluid (Kashyap et al, 2016), but no such literature is available on development of stem callus on MS medium, containing coconut water in combination with plant growth hormones, followed by impact of zinc sulphate for early rooting of the stem as well as estimation of the berberine content through HPLC and HPTLC methods.…”
Section: Introductionmentioning
confidence: 99%
“…Also, 100% in vitro rooting of Prunus empyrean was achieved on half strength MS medium supplemented with 0.5 mg L -1 IBA (Sadeghi et al, 2015). Senarath (2010) found that rooting percentage with full strength MS medium was significantly lower (20%) than half strength MS medium (100%) in the medicinal plant Coscinium fenestratum. Rooting in Pistacia vera shoots family Anacardiaceae was achieved on ½ MS medium supplemented with 2.5 mg L -1 IBA (Benmahioul, 2017).…”
Section: Rooting and Acclimatization Stagesmentioning
confidence: 90%
“…In all tested media in this experiment, AC was added in 1 g L -1 to avoid browning injuries. Senarath (2010) reported that browning is a major problem in plant tissue culture, so the juvenile sources in micropropagation is usually preferred in several plant species. Das and Srivastav (2015) found that explant death in Aloe vera can be caused by oxidation of phenolic compounds, which can be reduced by addition of AC at 2 g L -1 .…”
Section: Shoot Initiationmentioning
confidence: 99%
“…Similarly, in Vitex negundo, Sahoo and Chand (17) reported BAP as the most effective growth hormone for shoot bud induction. Multiple shoots were formed from epicotyl explants of Coscinium ferestratum on MS medium supplemented with cytokinins (18,19). Huetteman and Preece (20) reported that Thidiazuron is a potent cytokinin hormone used for the growth of woody plants in tissue culture.…”
Section: Discussionmentioning
confidence: 99%